Response to Conservative Treatment for Thumb Carpometacarpal Osteoarthritis Is Associated With Conversion to Surgery: A Prospective Cohort Study - Tsehaie, Jonathan (Phys Ther, 2019)
BACKGROUND: The current guidelines for treatment of carpometacarpal osteoarthritis recommend starting with conservative treatment before a surgical procedure is considered. OBJECTIVE: The objective was to investigate how response to conservative treatment, in terms of pain and hand function, influences the hazard that patients convert to surgical treatment. DESIGN: This was a multicenter, prospective cohort study. METHODS: Participants comprised 701 patients who received 3 months of hand therapy and an orthosis. Pain and function were measured with the Michigan Hand Questionnaire (MHQ) at baseline and at 6 weeks and 3 months follow-up. Conversion to surgical treatment was recorded from clinical records. Joint modeling (a statistical method of combining prediction models) was used to perform the analysis and to calculate hazard ratios (HRs). RESULTS: The joint analytical model showed that both MHQ pain score at a certain point (HR = 0.93; 95% confidence interval [CI] = 0.92–0.94) and change in MHQ pain score (HR = 1.07; 95% CI = 1.06–1.09) during conservative treatment was significantly associated with conversion to surgical treatment. The joint analytical model between functional outcome and conversion to surgical treatment showed only a significant association between MHQ function at a certain point (HR = 0.97; 95% CI = 0.95–0.99), and no significant association between the change in MHQ score for function (HR = 1.0; 95% CI = 1.0–1.0) and conversion to surgical treatment. LIMITATIONS: Missing data might have resulted in biased estimates. CONCLUSIONS: Self-reported pain and function, as well as change in self-reported pain during treatment, were associated with the hazard of conversion to surgical treatment, whereas change in self-reported functioning was not associated with conversion. Because a reduction in pain during conservative treatment appears to decrease the rate of conversion to surgical treatment, it is advised to structurally monitor pain levels during treatment. Listen to the author interview at https://academic.oup.com/ptj/pages/podcasts